A single amino acid residue controls ROS production in the respiratory Complex I from Escherichia coli. Issue 6 (29th October 2013) - Knuuti, Juho; Belevich, Galina; Sharma, Vivek; Bloch, Dmitry A.; Verkhovskaya, Marina
Summary Reactive oxygen species (ROS) production by respiratory Complex I from Escherichia coli was studied in bacterial membrane fragments and in the isolated and purified enzyme, either solubilized or incorporated in proteoliposomes. We found that the replacement of a single amino acid residue in close proximity to the nicotinamide adenine dinucleotide (NADH)‐binding catalytic site (E95 in the NuoF subunit) dramatically increases the reactivity of Complex I towards dioxygen (O2). In the E95Q variant short‐chain ubiquinones exhibit strong artificial one‐electron reduction at the catalytic site, also leading to a stronger increase in ROS production. Two mechanisms can contribute to the observed kinetic effects: (a) a change in the reactivity of flavin mononucleotide (FMN) towards dioxygen at the catalytic site, and (b) a change in the population of the ROS‐generating state. We propose the existence of two (closed and open) states of the NAD+‐bound enzyme as one feature of the substrate‐binding site of Complex I. The analysis of the kinetic model of ROS production allowed us to propose that the population of Complex I with reduced FMN is always low in the wild‐type enzyme even at low ambient redox potentials, minimizing the rate of reaction with O2 in contrast to E95Q variant.